2014
DOI: 10.1016/j.lfs.2014.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-primed exosomes mitigate endothelial cell dysfunction during hyperhomocysteinemia

Abstract: Aim Exosomes, the nano-units (<200nm), released from diverse cell types in the extracellular body fluid, possess non-immunogenic property and ability to cross blood-brain barrier (BBB). Since exosomes carry biological information from their cells of origin, we hypothesize that priming cells with potential therapeutic agents release improved cellular contents through exosomes. Curcumin possesses anti-oxidative, anti-inflammatory properties and provides a promising treatment for cerebral diseases and therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(74 citation statements)
references
References 35 publications
1
73
0
Order By: Relevance
“…Small lipophilic molecules, such as antioxidants, curcumin, and anticancer agents, can be passively loaded into EVs or EVMs by simple incubation 52, 93, 94. Drugs, including curcumin, show advanced stability and bioavailability when encapsulated compared to free‐state drugs and have been successfully used in preclinical research 95.…”
Section: Modular Design Of the Lipid Bilayermentioning
confidence: 99%
“…Small lipophilic molecules, such as antioxidants, curcumin, and anticancer agents, can be passively loaded into EVs or EVMs by simple incubation 52, 93, 94. Drugs, including curcumin, show advanced stability and bioavailability when encapsulated compared to free‐state drugs and have been successfully used in preclinical research 95.…”
Section: Modular Design Of the Lipid Bilayermentioning
confidence: 99%
“…urine, saliva, cerebrospinal fluid) and in conditioned cell culture media (12). They are formed in multivesicular bodies (MVB) inside the cells (5, 12). Exosomes naturally function as intercellular messengers, carrying RNA and proteins (13).…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes naturally function as intercellular messengers, carrying RNA and proteins (13). Recently, exosomes have begun to be explored for use as drug delivery vehicles for nucleic acids (14-19), gene delivery (20), and small molecule drugs, such as curcumin (12, 21, 22), and doxorubicin (23). It was demonstrated that exosomes have the exceptional ability to interact with cellular membranes, and deliver their payload to target cells (24, 25).…”
Section: Introductionmentioning
confidence: 99%
“…15 Exosomes (<200 nm) released from diverse cell types in the extracellular fluid are nonimmunogenic and possess the ability to cross the BBB. 45 Since exosomes carry biological information from their cells of origin, encapsulating or priming cells with potential therapeutic agents has been shown to improve cellular delivery through exosomes. Xin et al 46 suggested that intravenous administration of exosomes derived from mesenchymal stromal cells to a rat stroke model might improve functional recovery and enhance neurite remodeling, neurogenesis, and angiogenesis.…”
Section: Other Drug Delivery Optionsmentioning
confidence: 99%